Indonesia’s Identity and Norms in Response to the Nagorno-Karabakh Conflict in 2020: A Constructivism View - Imam Achmad Baidlowi; Hafid Adim Pradana (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2022)
The Nagorno-Karabakh conflict escalated again in 2020, confronting between Azerbaijan and Armenia. As the main actors of the conflict, have claimed approximately 5000 victims in the fighting that took place in the border areas of each of these countries. At that time there were 130 Indonesian citizens in Azerbaijan and 2 Indonesian citizens in Armenia. This situation certainly demands the attitude of Indonesia. Moreover, at that time Indonesia was serving as a Non-Permanent Member of the UN Security Council. This study seeks to examine the influence of identity and norms in Indonesia's response to the Nagorno-Karabakh conflict in 2020. The researcher uses a constructivist approach to the significance of the construction and Indonesian identity and norms. Researchers also try to analyze and describe the relationship between national identity and international norms with forms of response and Indonesian foreign policy. By using qualitative methods sourced from interviews with the Ministry of Foreign Affairs of the Republic of Indonesia, as well as literature studies to enrich data analysis. Through this framework, the author concludes that there are several identities that encourage Indonesia to respond to the Nagorno-Karabakh conflict. Namely the identity of the Preambule of the 1945 Constitution, the identity of an Islamic state, the identity of a free and active foreign policy, and an identity with fellow Islamic countries in the OIC. In addition to identity, Indonesia's response is also driven by the norms of Peace and War, both unwritten and institutionalized in the United Nations.